The Establishment of Mulla Sadra’s Philosophy: Main Concepts on Al-Hikmah Al-Muta’alliyah - Miswari Usman (At-Tafkir, 2022)
The purpose of this article is to review the main concepts of Mulla Sadra’s philosophy. These ideas are the foundation of the Al-Hikmah Al-Muta'alliyah group of philosophy theory. This philosophy, along with Al-Hikmah Al-Masya'iyyah and Al-Hikmah Al-Isyraqiyah, is one of the three major groups in Islamic philosophy. This study used a descriptive analysis. The author reviews the main work of Mulla Sadra, namely Al-Hikmah Al-Muta'alliyah fil Al-Sysfar 'Aqliyah Arba'ah and another book, namely Al-Masya'ir. Secondary references are also used, such as Mulla Sadra's other works and they’re relevant to the subject of study. This study attempts to identify the six concepts that make up the philosophical theory of Al-Hikmah Al-Muta'alliyah, namely: the fundamental of wujûd (Ashalat al- Wujûd), the gradation of wujûd (Tâskîkal-Wujûd), the poverty of cause (Illîyah), the simple reality (Basith al-Haqîqah), the substance movement (al-Harakah al-Jawhayiah), and the unity of subject and object (Ittihad Aqil wa Ma'qûl). These concepts demonstrate that Mulla Sadra's philosophy has strong conceptual roots and is difficult to refute. As a result, Mulla Sadra's philosophy remains one of the most influential groups of Islamic philosophy.